The Influence of Taxpayer Compliance Factors Toward Indonesian’s Personal Taxpayer - Agatha, Ade Wirianti; Sutrisno; Rusydi, Mohammad Khoiru (Accounting Department,, 2024)
Purpose — This research aims to evaluate and analyze the correlation between tax understanding and sanctions and taxpayer compliance while also investigating the role of risk preference and religiosity as moderating factors. Design/methodology/approach This investigation is an associative research study that employs a quantitative approach. It was conducted on individual taxpayers registered at the Bau-Bau Pratama Tax Service Office. The research sample included as many as 302 respondents. The data in this study were analyzed using multiple regression analysis using the statistical program Partial Least Square (PLS). Findings — The results show that (I) tax understanding has a positive effect on taxpayer compliance, and (II) tax sanctions have a positive effect on taxpayer compliance. (III) Risk preferences are proven to strengthen the effect of tax understanding on taxpayer compliance. (IV) Risk preferences have not been proven to strengthen the effect of tax sanctions on taxpayer compliance. (V) Religiosity is proven to strengthen the effect of tax understanding on taxpayer compliance. (VI) Religiosity is proven to strengthen the effect of tax sanctions on taxpayer compliance. Practical implications—This research can benefit taxpayers and tax authorities by improving taxpayer compliance. It can also encourage and motivate taxpayers to be more sensitive in fulfilling their obligations to pay taxes in accordance with applicable regulations so that taxpayers avoid tax sanctions or fines and understand all forms of tax regulations. Originality/value—This study presents a phenomenon related to taxpayer compliance in KPP Pratama Bau-Bau. It aims to analyze taxpayers and identify the causes of low taxpayer compliance in KPP Pratama Bau-Bau. This research is also a consideration for the Directorate General of Taxes regarding making regulations that can improve taxpayer compliance, especially for individual taxpayers registered with KPP Pratama Bau-Bau. Paper type — Quantitative research